Yin and yang roles of B lymphocytes in solid tumors: Balance between antitumor immunity and immune tolerance/immunosuppression in tumor-draining lymph nodes - Katakai, Tomoya (Frontiers in Oncology, 2023)
The role of B cells in antitumor immunity has been reported to be either promotive or suppressive, but the specific mechanism remains to be comprehensively understood. However, this complicated situation likely depends on the temporal and spatial relationship between the developing tumor and B cells that recognize tumor antigens. Unlike responses against microbial or pathogenic infections, tumor cells are derived from autologous cells that have mutated and become aberrant; thus, elimination by the adaptive immune system is essentially inefficient. If tumor cells can evade immune attack at an early stage, non-destructive responses, such as tolerance and immunosuppression, are established over time. In tumor-draining lymph nodes (TDLNs), tumor antigen-reactive B cells potentially acquire immunoregulatory phenotypes and contribute to an immunosuppressive microenvironment. Therefore, triggering and enhancing antitumor responses by immunotherapies require selective control of these regulatory B cell subsets in TDLNs. In contrast, B cell infiltration and formation of tertiary lymphoid structures in tumors are positively correlated with therapeutic prognosis, suggesting that tumor antigen-specific activation of B cells and antibody production are advantageous for antitumor immunity in mid- to late-stage tumors. Given that the presence of B cells in tumor tissues may reflect the ongoing antitumor response in TDLNs, therapeutic induction and enhancement of these lymphocytes are expected to increase the overall effectiveness of immunotherapy. Therefore, B cells are promising targets, but the spatiotemporal balance of the subsets that exhibit opposite characteristics, that is, the protumor or antitumor state in TDLNs, should be understood, and strategies to separately control their functions should be developed to maximize the clinical outcome.